Phase Ib Study of the Histone Deacetylase 6 Inhibitor Citarinostat in Combination With Paclitaxel in Patients With Advanced Solid Tumors - Gordon, Michael S.; Shapiro, Geoffrey I.; Sarantopoulos, John; Juric, Dejan; Lu, Brian; Zarotiadou, Angeliki; Connarn, Jamie N.; Le Bruchec, Yvan; Dumitru, Calin Dan; Harvey, R. Donald (Frontiers in Oncology, 2022)
Background: Citarinostat (CC-96241; previously ACY-241), an oral inhibitor of histone deacetylases (HDACs) with selectivity for HDAC6, has demonstrated synergistic anticancer activity with paclitaxel in multiple solid tumor models. Combination therapy using citarinostat with paclitaxel was evaluated in this phase Ib 3 + 3 dose-escalation study in patients with advanced solid tumors. Methods: Patients with previously treated advanced solid tumors received citarinostat 180, 360, or 480 mg once daily on days 1 to 21 plus paclitaxel 80 mg/m2 on days 1, 8, and 15 of 28-day cycles until disease progression or unacceptable toxicity. The primary endpoint was determination of the maximum tolerated dose (MTD). Secondary endpoints included safety, antitumor activity, pharmacokinetics, and pharmacodynamics. Results: Twenty patients were enrolled and received study treatment; 15 had received prior taxane therapy. No dose-limiting toxicities were reported at any dose; therefore, the MTD was not identified. Citarinostat 360 vs 480 mg was associated with reduced incidence and severity of neutropenia. Three patients experienced a confirmed partial response and 13 achieved stable disease. Pharmacokinetic parameters were linear up to citarinostat 360 mg, the dose at which the highest levels of histone and tubulin acetylation were observed in peripheral blood mononuclear cells. Conclusions: The combination of citarinostat plus paclitaxel showed an acceptable safety profile, with no unexpected or dose-limiting toxicities and potential evidence of antitumor activity in patients with heavily pretreated advanced solid tumors. Citarinostat 360 mg once daily is considered the recommended phase II dose for use in combination with paclitaxel 80 mg/m2 every 3 of 4 weeks. This trial is registered on ClinicalTrials.gov (NCT02551185).